Case study on lightning protection system in term of collection volume method at Faculty of Science Computer and Mathematics in Universiti Teknologi MARA Shah Alam / Nurhafizaturrafizah Ibrahim - Ibrahim, Nurhafizaturrafizah (2014)
This paper describes the study on the risk assessment of lightning protection at Faculty of Science Computer and Mathematics building. Risk assessment is a process in order to detect potential hazard and analyses the possible occurrences happen towards the building and assets by using the suitable Lightning Protection System (LPS). The study based on the respective building in order to reduce the risk of damage of electric and electronic equipment due to lightning strikes. The risk of the building will be determined based on Malaysian Standard Lightning Protection System MS 62305. In this Malaysian Standard, it is divided into 4 parts which are general principles, risk management, physical damage to structures and life hazard and electrical and electronic systems within structures. Basically, this thesis will be covered by comparing the tolerable risk (RT) with all relevant risk components (Ri) .If Ri > RT, the protection should consider suitable protection measures in order to reduce the risk due to lightning flashes. Several mathematical parameters need to be taken into consideration while assessing of the risk evaluation. The recommended method for this project is Collection Volume Method (CVM). The methods had been evaluated and been discussed looking for any improvement and reliability regarding the risk assessment at respective building. At the end of this paper, the analyses data will represent the reliability or any improvement towards building location in term of reducing the risk due to the lightning.